(3eSGdc GdCagGe TQM TQGFY GdESdGes - (3GdYGedj GdLYHj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, (B966 (3g`s ((3eMeO QVG Hf Ydj Hf NGf GdLQaGObGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3agPg fcJ eNJUQg hahGFO eMHQg hUZJgG Ydi cJGH TQGFY GdESdGe HGdJeGS LeGYI ef GdeNdUjf GdCYdGe JbjO eWdbgG hJHjf eLedgG hJSgd eYXdgG JZfj GdeTJZd HGdcJGH ef CSaGQ cHGQ hJWdYg Ydi ObGFb (B...s
(3BNQgG (B:s
... (3hdh Mce HePgH Cgd GdNdGa eY EecGf GfaGOg GdMb cGf OGFeG VGefG hbO JbOe GdcdGe aj GSJKfGA GdbJd hGdLQM ef GdEcQGg aEfg (B.. (3hGddg Gdehabs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\64s
(3eYLe GdeDdajf (B1\741s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis